2010
DOI: 10.1111/j.1574-6941.2009.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and activity are increased by compost amendment of metal-contaminated soil

Abstract: Unlike organic pollutants, heavy metals cannot be degraded and can constitute a persistent environmental hazard. Here, we investigated the success of different remediation strategies in promoting microbial diversity and function with depth in an acidic soil heavily contaminated with Cu, Pb and Zn. Remediation involved the incorporation of either a high-or a low-quality compost or inorganic fertilizer into the topsoil and monitoring of microbial activity and diversity with soil depth over a 4-month period. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Alvarenga et al (2007) reported that sewage sludge amendment increased soil protease and urease activities, while the application of garden waste compost had no influence on their activities in an acid metal-contaminated soil affected by mining activities. Farrell et al (2010) demonstrated that soil microbial biomass carbon (MBC) and basal respiration were improved after incorporation of green waste-derived compost into an acidic soil contaminated with Cu, Pb and Zn at Parys Mountain, Anglesey, North Wales.…”
Section: Introductionmentioning
confidence: 99%
“…Alvarenga et al (2007) reported that sewage sludge amendment increased soil protease and urease activities, while the application of garden waste compost had no influence on their activities in an acid metal-contaminated soil affected by mining activities. Farrell et al (2010) demonstrated that soil microbial biomass carbon (MBC) and basal respiration were improved after incorporation of green waste-derived compost into an acidic soil contaminated with Cu, Pb and Zn at Parys Mountain, Anglesey, North Wales.…”
Section: Introductionmentioning
confidence: 99%
“…to alleviate the deficient fertility conditions for plant growth in mine tailings (e.g. Farrell et al, 2010;Soler-Rovira et al, 2010;Clemente et al, 2012;Kohler et al, 2014). Due to their heterogeneous nature, municipal solid wastes may show high variability in composition and properties.…”
Section: Suitability Of the Addition Of Municipal Solid Wastes On Minmentioning
confidence: 99%
“…It provides quantitative data on microbial communities [16]. As another simple, rapid and molecular technique, denaturing gradient gel electrophoresis (DGGE) can provide information on dominant microbial species such as bacteria, fungi, and target groups by the use of different primers in the same soil DNA extract [17].…”
Section: Introductionmentioning
confidence: 99%